Desain Sistem Pendataan Kependudukan dan Keluarga Oleh TPK-BKKBN di Kelurahan Kenali Asam Kecamatan Kota Baru Jambi - Fikri Haikal; Mutamassikin Mutamassikin; Albert Triadi (Global Leadership Organizational Research in Management, 2025)
As a team under the auspices of the BKKBN service, it has an important role in managing data such as birth data, deaths, stunted toddler data and others. However, at the end of the agency, namely cadres, they still do manual data collection, with manual recording in books. An information system is needed so that cadres are able to assist in inputting data processing data so that the data reporting process becomes faster, more efficient, smoother and will also have an impact on improving work operations. The design uses an entity relationship diagram to be able to clarify the purpose of the design made. The results of the system display are also in accordance with the design of the system display, have a logo from BKBBN because the Family Assistance Team is under the auspices of BKKBN. When the dashboard display is given a welcome greeting, to the login page. Researchers also try to apply all data structure designs, starting from the design of the profile data structure, the password change data structure, the toddler data structure, the pregnant woman data structure, the catin data structure, and the report data structure. The author produces a feasible system design that is very much in accordance with user needs, using Figma software. The design of the Family Assistance Team data recording information system in Kenali Asam Village, Kota Baru District, Jambi is feasible because it is in accordance with the needs